Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 3 - Adding and Subtracting Fractions - 3.3 Adding and Subtracting Unlike Fractions - 3.3 Exercises: 23

Answer

$ \frac{1}{2}$.

Work Step by Step

$\frac{5}{6} - \frac{1}{3} = \frac{5}{6} - \frac{1 \cdot 2}{3 \cdot 2} = \frac{5}{6} - \frac{2}{6} = \frac{5 - 2}{6} = \frac{3}{6} = \frac{1}{2}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.